The Future of Law Firms (and Lawyers) in the Age of Artificial Intelligence - Anthony E. Davis (Revista Direito GV)
Abstract This article explores the future for lawyers and law firms in the light of the changes that Artificial Intelligence (“AI”) is already bringing to the universe of legal services. Part I briefly describes some of the ways AI is already in use in ordinary life - from facial recognition, through medical diagnosis to translation services. Part II describes how AI is transforming what it means to provide legal services in six primary areas: litigation review; expertise automation; legal research; contract analytics; contract and litigation document generation; and predictive analytics. Part III explores who are the providers of these AI driven legal services - often non-lawyer legal service providers - and how these providers are replacing at least some of what clients have traditionally sought from lawyers. Part III also discusses the implications of all these changes both for the future role of lawyers individually, and in particular what services will clients still need lawyers to perform: judgment, empathy, creativity and adaptability. In turn, this Part examines what will these changes mean for the size, shape, composition and economic model of law firms, as well as the implications of these changes for legal education and lawyer training. Part IV identifies the principal legal, ethical, regulatory and risk management issues raised by the use of AI in the provision of legal services. Finally, in Part V the article considers who will be the likely providers of AI based services other than law firms: legal publishers, major accounting firms and venture capital funded businesses.